Fertility outcomes and predictors for successful sperm retrieval and pregnancy in 327 azoospermic men with a history of cryptorchidism who underwent microdissection testicular sperm extraction - Cayan, Selahittin; Orhan, Irfan; Altay, Baris; Asci, Ramazan; Akbay, Erdem; Ayas, Bulent; Yaman, Onder (Wiley, 2021)
Background Although few studies have reported fertility outcomes, no study has reported risk factors that might predict sperm retrieval and pregnancy in azoospermic men with a history of cryptorchidism in a large series. Objectives To investigate fertility outcomes and predictors for successful sperm retrieval and pregnancy in azoospermic men with a history of cryptorchidism who underwent microdissection testicular sperm extraction (mTESE). Materials and methods This retrospective observational study included 327 azoospermic men with a history of cryptorchidism who underwent mTESE. Fertility outcomes including sperm retrieval, fertilization rate, number of transferred embryos, pregnancy, miscarriage, and live birth rates were recorded. Results Sperm retrieval was observed in 172 (52.6%) of the patients. The mean fertilization, pregnancy, and live birth rates were 55.2%+/- 20.5, 53.5%, and 44.8%, respectively. The sperm retrieval rate was significantly higher at the orchidopexy age of <= 9.5 years (70.8%) than the orchidopexy age of > 9.5 years (42.1%) (P = .000). Patients with total testicular volume of >= 13.75 mL had significantly higher sperm retrieval rate (65.2%) than the patients with total testicular volume of < 13.75 mL (45.5%) (P = .001). Patients with total testosterone level of >= 300.5 ng/dL had significantly higher sperm retrieval rate (65.6%) than the patients with total testosterone level of < 300.5 ng/dL (40.3%) (P = .000). Patients with follicle-stimulating hormone (FSH) level of <= 17.25 mIU/ml had significantly higher sperm retrieval rate (72.3%) than the patients with FSH level of > 17.25 mIU/mL (44.4%) (P = .000). Younger male and female ages, and higher fertilization rates were the parameters that might predict pregnancy. Conclusions Infertile azoospermic men with a history of cryptorchidism have high sperm retrieval rate with mTESE. Patients who had orchidopexy at the age of <= 9.5 years, and having total testicular volumes of >= 13.75 mL with total testosterone level of > 300.5 ng/dL and FSH level of <= 17.25 mIU/mL have higher success rate for sperm retrieval.
Keywords: cryptorchidism; orchidopexy; sperm retrieval; pregnancy; predictors